PENGARUH PENGGUNAAN BIOSUPLEMEN BAKTERI UNGGUL ASAL RAYAP TERHADAP ORGAN DALAM ITIK BALI JANTAN - G. I. R., Dwipayana; Dewi, G. A. M. K.; Sutama, I N. S.; Mudita, I M. (Jurnal Peternakan Tropika, 2017)
This study aimed to determine the effect  of using superior termites bacteria biosupplement in ration on the internal organ of bali drakes up to 12 weeks of age. this experiment used of 75 birds with homogenuous body weight ( 223,8 ± 11,19 g). The experimental design used in this study was complettely randomized design (CRD) with 5 treatments and 3  replicated those of  RB, RBio 0 , RBio 1 , RBio 2 , RBio 1-2 treatments were duck fed basal ration, fed basal ration with biosupplement without superior termites bacteria, fed basal ration with biosupplement containing superior 1 termites bacteria, fed basal ration with biosupplement containing superior 2 termites bacteria, fed basal ration with biosupplement containing combination superior 1 and 2 termites bacteria respectively. The variables were observed were the heart weight, liver weight, bile weight and spleen weight. The results of this study showed that fed biosupplement containing combination superior for variable of heart weight, liver weight, bile and spleen weight, fed biosupplement superior bacteria termites in basal ration were not significant different (P>0,05).
Keywords: Biosupplerment, Superior Termites Bacteria, Internal Organs, Bali Drakes